2016
DOI: 10.1002/adma.201505491
|View full text |Cite
|
Sign up to set email alerts
|

Ultrapure Blue Thermally Activated Delayed Fluorescence Molecules: Efficient HOMO–LUMO Separation by the Multiple Resonance Effect

Abstract: Ultrapure blue-fluorescent molecules based on thermally activated delayed fluorescence are developed. Organic light-emitting diode (OLED) devices employing the new emitters exhibit a deep blue emission at 467 nm with a full-width at half-maximum of 28 nm, CIE coordinates of (0.12, 0.13), and an internal quantum efficiency of ≈100%, which represent record-setting performance for blue OLED devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
1,454
2
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,534 publications
(1,509 citation statements)
references
References 27 publications
35
1,454
2
18
Order By: Relevance
“…Some of them even show CIE coordinates of (0.15, 0.09) and (0.15, 0.08) for the PL of emitters in toluene but none of them gave OLEDs with colour coordinates satisfying or being close to the NTSC blue standard of CIE coordinates (0.14, 0.08) [94]. Recently, Hatakeyama et al reported a new strategy to design effective deep blue triarylboron based emitters [95]. The chemical structures of boron emitters (28)(29) are given in Figure 6, while their novel design strategy is displayed in Figure 7.…”
Section: Triarylborane Emittersmentioning
confidence: 99%
“…Some of them even show CIE coordinates of (0.15, 0.09) and (0.15, 0.08) for the PL of emitters in toluene but none of them gave OLEDs with colour coordinates satisfying or being close to the NTSC blue standard of CIE coordinates (0.14, 0.08) [94]. Recently, Hatakeyama et al reported a new strategy to design effective deep blue triarylboron based emitters [95]. The chemical structures of boron emitters (28)(29) are given in Figure 6, while their novel design strategy is displayed in Figure 7.…”
Section: Triarylborane Emittersmentioning
confidence: 99%
“…However, high-performance blue TADF emitters are still very rare and only a few of them can achieve both a high external EL quantum efficiency ( η ext ) exceeding 20% and a suitable color purity with a CIE y value below 0.25. 10,16,21,22,29,33,34,38 Hence, it remains quite challenging to search for an appropriate combination of D and A moieties to simultaneously attain both excellent EL efficiency and high color purity for deep-blue TADF materials.…”
Section: Introductionmentioning
confidence: 99%
“…12). [82][83][84] A representative example of 9-([1,1′-biphenyl]-3-yl)-N,N,5,11-tetraphenyl-5,9-dihydro-5,9-diaza-13b-boranaphtho[3,2,1-de]anthracen-3-amine (DABNA-2) developed by Hatakeyama et al 82 realized a high EQE of 20% and a very narrow full-width at half-maximum of 28 nm. Furthermore, Mamada et al 83 presented a whole new type of planar TADF emitter based on the use of excitedstate intramolecular proton transfer without conventional D-A structures.…”
Section: Discussionmentioning
confidence: 99%